PENDEKATAN NARRATIVE DALAM PERANCANGAN KONEKTIVITAS RUANG SEMPADAN DI JALAN TAMAN KEMANG (ATRIUM Jurnal Arsitektur, 2019)
Title: Narrative Approach in the Design of Integrated Space Connectivity in Taman Kemang As a commercial area the Taman Kemang street has certain activities based on its functions such as parking ,working, selling (street vendors), eating and relaxing, people who just walk to Lippo Mall Kemang and activities from online transportation to deliver and pick up. However, as a commercial area, the Taman Kemang street does not have the balance of the daily activities as the city space. This is because different activities are defined by time from morning to night and weekdays and weekends. This is because the bordering space that are formed are utilized as parking lots and selling places of the street vendors which it should be utilized more as public spaces. Therefore, in this research, the author uses a narrative approach as an analysis process towards the design stage through the stages of the story - narrative - narration as a problem-solving solution. The process of analysis is based on activities on the Taman Kemang street through the motives of community activities that form events in a certain time. So that in the narrative stage a story concept is formed which is how to revive the bordering space of the daily narrative formed on the Taman Kemang street. Then supported by strategies at the stage of narration through 5 narrative landscape strategies and forming quality space, namely the formation of activity identity, space identity and continuity of the results of the integration of bordering space elements.